Pelaksanaan Teknik Budidaya Kelapa Sawit (Elaeis Guineensis Jacq) Swadaya Masyarakat di Lahan Pasang Surut Kecamatan Bangko Pusako Kabupaten Rokan Hilir - Santoso '; Sampoerno '; Gulat ME Manurung (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aims to determine the implementation of non-governmental palm oil cultivation techniques (Elaeis guineensis Jacq) in tidal area on Bangko Pusako District Rokan Hilir Regency. The research was conducted on tidal land at the village of Bangko Kanan and Bangko Kiri in Bangko Pusako District Rokan Hilir Regency, from April to July 2013. This study was conducted using survey and processed data presented in descriptive form. The number of respondents in this study were 40 respondents, based on 5% level of representation. 17 respondents drawn from the Bangko Kanan and 23 respondents drawn from the Bangko Kiri. The parameters studied were the origin of the seeds, plant spacing, size of planting holes, transplanting seedlings to the field, eradication of weeds, fertilizing, castration, plant population/ha, water level measurements and measurements of distance of land from the river. The results show that the average production of farmers palm oil are still very low at less than 50% when compared to the average production of palm oil of PTPN V on mineral lands in general. The low production of palm oil cultivation techniques of farmers due to conducted as seed origin, plant spacing, pattern spacing, the size of the planting hole, transplanting seedlings into the ground, fertilizing, castration and plant population/ha are still quite low level of the appropriate palm oil cultivation techniques application in the field. Keywords: Palm Oil Cultivation, Tidal Area, Rokan Hilir Regency